Progress of the microfinance sector in Albania, current challenges and the perspective of this sector - Fabian Pjetri; Rajs Kastrati; Fjorda Prifti (Agora International Journal of Economical Sciences (AIJES), 2024)
The paper presented by the authors aims to research the role of Microfinance in Albania over the years, especially in improving living conditions for the less privileged groups. The authors have tried to give a summarized panorama regarding the progress and evolution of Microfinance in the state of Albania. Portraying the latter as a good alternative solution to the shortcomings of the Traditional Banking System, to address the needs of certain segments of the population. The analysis used by the authors focuses on the major and current challenges that the Microfinance sector in Albania is facing, it also examines the perspectives and potential future opportunities of this developing sector in our country. Since most of the economic entities that operate in our country are small and medium-sized businesses, where family businesses account for a significant number of the total number of economic entities, the authors have considered it important to research this segment of the economy.
Keywords: 330